Electrochemical microfluidic immunosensor based on TES-AuNPs@Fe3O4 and CMK-8 for IgG anti-Toxocara canis determination - Jofre, Claudio Francisco (2020)
We report a microfluidic immunosensor for the electrochemical determination of IgG antibodies anti-Toxocara canis (IgG anti-T. canis). In order to improve the selectivity and sensitivity of the sensor, core-shell gold-ferric oxide nanoparticles (AuNPs@Fe3O4), and ordered mesoporous carbon (CMK-8) in chitosan (CH) were used. IgG anti-T. canis antibodies detection was carried out using a non-competitive immunoassay, in which excretory secretory antigens from T. canis second-stage larvae (TES) were covalently immobilized on AuNPs@Fe3O4. CMK-8-CH and AuNPs@Fe3O4 were characterized by transmission electron microscopy, scanning electron microscopy, energy dispersive spectrometry, cyclic voltammetry, electrochemical impedance spectroscopy, and N2 adsorption-desorption isotherms. Antibodies present in serum samples immunologically reacted with TES, and then were quantified by using a second antibody labeled with horseradish peroxidase (HRP-anti-IgG). HRP catalyzes the reduction from H2O2 to H2O with the subsequent oxidation of catechol (H2Q) to p-benzoquinone (Q). The enzymatic product was detected electrochemically at _100 mV on a modified sputtered gold electrode. The detection limit was 0.10 ng mL−1, and the coefficients of intra- and inter-assay variation were less than 6%, with a total assay time of 20 min. As can be seen, the electrochemical immunosensor is a useful tool for in situ IgG antibodies anti-T. canis determination.